ANALISIS IMPLEMENTASI KEBIJAKAN AKT]NTANSI BADAN LAYANAN UMUM (studi kasus PTN BLU X) - , Ristina Rahmawati ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Badan Layanan Umum (BLU) is a financial report scheme for Public Services Unit as part of government system, which consist of one or more accounting entities that according to law has the responsibility to deliver the following financial reports: balance sheet, activity report, cash-flow report, and other financial notes. Rules on the implementation of BLU financial report scheme is still on the general level, affecting to some difficulties in its implementation, since each public service units under the government has varied characteristics. This research aimed to measure the suitability of financial policy applied by University X as one of BLU universities in making its financial report with the accounting policy explained in PMK/ Financial Minister Decree No 76 year 2008. This research also aimed to picture and analyzes the implementation of financial report as well as identifying and explaining the obstacles in making the financial report. This research is done using the qualitative method. The data for the research is collected through active observation and document collection. In analyzing the data, descriptive analysis method is used. The result of data analysis shows that the rate of suitability between the accounting policy applied by university X using the BLU financial report scheme, compared to the accounting policy explained in PMK/ Financial Minister Decree No 76 year 2008 is 77,61%. The implementation of financial report of university X already referred to the guidance of accounting system of the university. Some of the obstacles in making the financial report in accordance to BLU Financial report scheme are the classification of fee which consist of service fee and general administration fee is not yet accommodate, financial information system which is not yet integrated, and difficulties in calculating the intangible assets such as intellectual property.